Deconstructing the Low-Vol Anomaly - Beveratos, Alexios; Bouchaud, Jean-Philippe; Ciliberti, Stefano; Laloux, Laurent; Lempérière, Yves; Potters, Marc; Simon, Guillaume (Journal of portfolio management, 2017)
The authors study several aspects of the so-called low-vol and low-β anomalies, some of which are already well documented (such as the universality of the effect over different geographical zones) and others hitherto not clearly discussed in the literature. The most significant message of the article is that the low-vol anomaly is the result oftwo independent effects. One is the striking negative correlation between past realized volatility and dividend yield. Second is the fact that ex-dividend returns themselves are weakly dependent on the volatility level, leading to better risk-adjusted returns for low-vol stocks. The authors find that this effect is further amplified by compounding. It appears that the low-vol strategy is not associated with short-term reversals, nor does it qualify as a risk premium strategy, because its overall skewness is slightly positive. For practical purposes, the strong dividend bias and resulting correlation with other valuation metrics (such as earnings/price or book/price) do make the low-vol strategies to some extent redundant, at least for equities.